Investigation on stimulated brillouin scattering (SBS) in the generation of self-seeded multiple wavelength brillouin erbium fiber laser (BEFL) / Mohd Ruzaleh Nurdik - Nurdik, Mohd Ruzaleh (2014)
Erbium-doped Fiber Laser (EDFL) configured into ring cavity system shows better performance compare to linear cavity fiber laser system. Ring cavity fiber laser has the advantage of higher efficiency, higher output power, and higher signal-to-noise ratio (SNR). Thus, the ring cavity laser configuration is preferred to be employed in the selfseeded Brillouin Erbium Fiber Laser (BEFL) system to generate the self-seeded multiple Brillouin Stokes.The Brillouin Fiber Laser (BFL) has been investigated in single and double ring cavity system to produce maximum number of Stokes signals. For a single cavity system, 7 and 9 Stokes signals were produced compare to 2 Stokes signals before enhancing at Brillouin pump (BP) source and configured an S-Shape in the cavity, respectively. In a double ring cavity BFL, 5 Stokes signals were generated and when configuration was enhanced by Erbium Doped Fiber Amplifier (EDFA) in the cavity, 8 Stokes signals were achieved. The BEFL which is the hybrid of BFL and EDFL shows improvement on the stokes generated when enhanced by EDFA where 14 Stokes were obtained. The optimization of BP power as lower as 2 dBm was able to produce a maximum 17 Stokes signals. This thesis focuses on the exploitation of non linear effects in Single-Mode Fiber (SMF), mainly the Stimulated Brillouin Scattering (SBS) in generating self-seeded multiple wavelength BEFL in double ring cavity. More than 67 multiple wavelengths self-seeded with 0.088 nm lines spacing were generated in 5.64 nm wavelength range from 1528.19 to 1533.83 nm and centered at 1531.01 nm. The signal to noise ratio of the spectrum is more than 16 dB. The injected 980 nm laser diodes (LDs) were set to optimum powers of 100 mW for pumping two erbium doped fibers in the two lasers cavities. The multiwavelength self-seeded has a good potential application in wavelength division multiplexing (WDM) especially in Dense Wavelength Division Multiplexing (DWDM) for data transmission in communications system.